Beyond arrival – On the potential and shortcomings of modularity in shelter and housing for the displaced - Yona Catrina Schreyer (Agathón, 2023)
Architecture comes to be a tangible reflection of significant contemporary events, offering insight into how designers respond to the challenges at hand. Particularly amid extreme circumstances necessitating swift spatial interventions, such as the sudden surge in demand for housing after a disaster, modularity appeals due to its potential for streamlining and scalability. This article explores how the module – both as a design concept and a construction method – can facilitate immediate design responses to accommodate large groups of people during sudden mass migration. It discusses the weaknesses of modularity, such as duration or materiality, critically reflects on standardised living modules, and questions a lack of urban stimulus amid the pressing need for increased permanent housing stock.